1995
DOI: 10.1002/psc.310010406
|View full text |Cite
|
Sign up to set email alerts
|

Conformational studies on synthetic peptides reproducing the dibasic processing site of pro‐ocytocin–neurophysin

Abstract: Synthetic peptides reproducing the proteolytic processing site of pro-ocytocin were studied by different spectroscopic techniques, including circular dichroism, Fourier transform infrared absorption, and mono and bidimensional nuclear magnetic resonance, in order to ascertain the possible role of three-dimensional structure in the recognition process by maturation enzymes. Experimental results were compared with energy minimization calculations and suggest that: (i) the region situated on the N-terminus of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…The i-turn motif seems, then, a quite general motif for those prohormone molecules where cleavage occurs in the proximity of a dibasic Arg-Lys pair. This has already been suggested in the case of pro-ocytocin fragments [4,5] and is confirmed again in the present study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The i-turn motif seems, then, a quite general motif for those prohormone molecules where cleavage occurs in the proximity of a dibasic Arg-Lys pair. This has already been suggested in the case of pro-ocytocin fragments [4,5] and is confirmed again in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…In recent years numerous studies have been made on the characterization of the structural parameters that are thought to play a key role in the enzymeprohormone recognition process [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The assumption that this new unbound state has the same stability to denaturation as unliganded mature NP leads to the results presented here. Relevant in this context is the fact that modeling studies have suggested conformational differences between the internally bound state of the bovine oxytocin precursor and the corresponding processed complex (38), and that structural studies of synthetic peptides representing the first 20 residues of the bovine oxytocin precursor suggest an influence of the GlyLys-Arg linker sequence on local structure in this region (39,40). The low effective intramolecular concentration of oxytocin within the precursor indicates that the internal free energy cost associated with bringing oxytocin and NP together approaches in magnitude the translational and rotational entropy loss associated with the bimolecular reaction and/ or that some of the secondary interactions (those not involving the hormone amino group or tyrosine) between oxytocin and NP in the intermolecular complex (6) are absent in the precursor.…”
Section: Discussionmentioning
confidence: 97%
“…Preliminary FTIR experiments performed in our laboratories with synthetic fragments, representing the processing site of proocytocin–neurophysin (pro‐OT/Np), in the presence of solvents unable to donate protons, such as dimethylsulfoxide (DMSO),22 indicated that H → D substitution on the amide function of peptide groups induces modifications of both the position and the intensity of the amide I band. The effects of the isotopic substitution were observed in the 1710–1670 and 1670–1650 cm −1 regions, which are attributable to α‐turns and β‐helices, respectively.…”
Section: Introductionmentioning
confidence: 99%